Orthogonal Generalized Derivation and Left (Resp. Right) Centralizers on Semiprime Ring - Hanan Khalid Mousa; Salah Mehdi Salih (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The object of this article is present the orthogonally of different two concepts. We proved: Assume and are orthog gd and l(rr)c on 2-tortion free semiprime ring s.t. is commutative then and are orthog where is associated derivation of .